Kecenderungan Neurotik Dan Sosiopatik - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1989)
ABSTRAK Drug abusers frequently show some symptoms of either neurotic or antisocial personality disorders, i.e., adaptation disorder or social maladaptation. The Manson Inventory was used to evaluate the personality aptitude of 25 cases and 25 controls. The results indicate that significantly more cases have neurotic and sosiopathic tendencies. They were followed in about four years until now, actually the aptitude changes into real disorder, neurotic and sosiopathic or antisosial personality.